Analysis of Readiness to Implement the Independent Curriculum Learning in The Era of Society 5.0 In Madrasah Aliyah Negeri in Batanghari Regency - Melisa Melisa; Lukman Hakim; Sya'roni (Dinasti International Journal of Education Management And Social Science, 2023)
This research was conducted at MAN 1 Batanghari and MAN 5 Batanghari. This research focuses on the application of the independent learning curriculum in state aliyah madrasahs in the era of society 5.0, teacher constraints in implementing the independent learning curriculum in the era of society 5.0 and teacher efforts in overcoming these obstacles. The results of researchers on the implementation of the independent learning curriculum in the era of society 5.0 in state aliyah madrasahs in Batanghari district, in MAN 1 Batanghari the implementation of the independent learning curriculum in the era of society 5.0 is quite good seen from teachers who have implemented an independent curriculum in grades X and XI for approximately 2 years, In its application, teachers have used technological devices such as: laptops, infocus, power point applications, google meet, and youtube. The obstacles faced by teachers in implementing the independent learning curriculum in the era of society 5.0 at MAN 1 Batanghari are the lack of information and communication technology skills of teachers, both facilities are still insufficient. Efforts to overcome the obstacles faced are by attending training or training on ICT, Work and improve discussions with fellow teachers. Furthermore, in MAN 5 Batanghari the implementation of the independent learning curriculum in the era of society 5.0 is not optimal enough, because the implementation is quite new so it is still in the adjustment stage, but in its application teachers have used ICT devices such as: Laptops, infocus, power point applications, and youtube. The obstacles faced by teachers in implementing the independent learning curriculum in the era of society 5.0 at MAN 5 Batanghari are the first teachers who find it difficult to change old mindsets or habits in teaching, secondly lack of information and communication technology skills of teachers, but facilities are still insufficient. Efforts to overcome the obstacles faced are by expanding knowledge and trying new things including varied methods of learning. by attending training or training on ICT, working and improving discussions with fellow teachers.